If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5) + 9 = 12 Reorder the terms: 3(-5 + 2x) + 9 = 12 (-5 * 3 + 2x * 3) + 9 = 12 (-15 + 6x) + 9 = 12 Reorder the terms: -15 + 9 + 6x = 12 Combine like terms: -15 + 9 = -6 -6 + 6x = 12 Solving -6 + 6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 12 + 6 6x = 12 + 6 Combine like terms: 12 + 6 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| 20n=m | | m=20n | | 2x-2y+z=7 | | x-4-13x-2+36=0 | | x^2-16x-29=0 | | (11b-8)-5(2b+4)=-6 | | 9m=7 | | 8x+6x+3+9=9x+5+4x | | 2y^2+2y+2=14 | | x^2+5x-6=2x+4 | | 15x+15y=8xy | | -9(v+4)+3v+5=5v+12 | | 7p+8=16+6p | | S(t)=-16t^2+64t+80 | | C(x)=5x^2-30x+81 | | 18w-(16w)= | | 8(4x+4)-4-6= | | 3x^2+-29x+40=0 | | m(p+2)=n | | 5[x-(4x-5)]=3-2x | | 9m^2-36m=0 | | 0.30x+0.30(30)=0.15(84) | | 2z^2+11z+12=0 | | 9x^2-57xy-42y^2=0 | | 5-21y+4y^2=0 | | -6x^2+47x+8=0 | | 27x^2-342x-72=0 | | 3v^2=8v+3 | | 0.04x-0.2=0.07 | | 3b^2-8b+5=0 | | 6(5s-11)-12(2s+5)=0 | | 5x+y+7=0 |